1997
DOI: 10.1002/(sici)1520-6866(1997)17:4/5<157::aid-tcm3>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on the assessment of the toxicity of “dioxins” for humans, using data from experimental and epidemiological studies

Abstract: "Dioxins" (polyhalogenated dibenzo-p-dioxins and dibenzofurans, PHDDs/PHDFs) have gained considerable scientific interest, and (unjustified or justified) also received tremendous political attention. The data pool available on sources, distribution in the environment, kinetics in animals and humans, and on biological and toxic actions in various species (including humans), is one of the largest among all environmental organic substances; but quality and predictive power of the data on possible effects in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 88 publications
(132 reference statements)
1
0
0
Order By: Relevance
“…In conclusion and in accordance with the literature (3)(4)(5)(6)(7)13,24,25), we found that our patients' chloracne and gastrointestinal symptoms were associated with TCDD intoxication, but, even in case of severe poisoning, this was not indicated by our routine laboratory investigation. In Patient 1, the disfiguring course of chloracne, which was unresponsive to isotretinoin, was most impressive, whereas only a mild expression of chloracne was present in Patient 2 despite the high TCDD blood level.…”
Section: Resultssupporting
confidence: 92%
“…In conclusion and in accordance with the literature (3)(4)(5)(6)(7)13,24,25), we found that our patients' chloracne and gastrointestinal symptoms were associated with TCDD intoxication, but, even in case of severe poisoning, this was not indicated by our routine laboratory investigation. In Patient 1, the disfiguring course of chloracne, which was unresponsive to isotretinoin, was most impressive, whereas only a mild expression of chloracne was present in Patient 2 despite the high TCDD blood level.…”
Section: Resultssupporting
confidence: 92%